Digital Transformation of Public Services: Evaluation of the Jakarta Kini (JAKI) Application in Jakarta’s Special Capital Region - Eko Ramadhan; Erdy Saparudi; Galang Persada Nurani Hakim (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2025)
Jakarta Kini (JAKI) is a digital service innovation initiated by the Provincial Government of Jakarta through the Jakarta Smart City program as an effort to apply information and communication technology in public administration. This study aims to analyze public perceptions of the effectiveness of JAKI in improving the quality and accessibility of public services in Jakarta. The research employs a descriptive qualitative approach with secondary document analysis derived from official reports, academic publications, and application performance data. JAKI is positioned as a regional model of smart governance that integrates multiple public services into a single digital platform. Unlike previous studies that mainly focused on technological aspects or user satisfaction, this study highlights the interconnection between government digital innovation and citizen participation within a data-driven public service ecosystem. The findings indicate that JAKI plays a substantial role in accelerating citizen reporting, expanding service accessibility, and strengthening participatory governance in digital administration. Early features such as JakLapor, JakRespons, JakPantau, and JakWarta serve as key foundations for two-way communication between the government and citizens. Meanwhile, new developments such as the Health Facility Queue Service, JKN Mobile Integration, Early Warning Notifications, and JakCare further enhance the platform’s role as an integrated digital service hub. Nevertheless, JAKI’s implementation remains suboptimal due to challenges related to uneven digital literacy, limited technological infrastructure, and data protection issues.